STRATEGI PENERAPAN 7 KEBIASAAN ANAK HEBAT OLEH ORANG TUA DAN GURU DI SEKOLAH DASAR - Mardiana Anjani Alamsyah; Lailiatul Hidayati; Erna Yayuk (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the strategies of parents and teachers in shaping children's character through the “7 Habits of Great Children” program in elementary schools, which is rooted in the concept of Leader in Me by Stephen Covey. This program aims to instill positive habits consistently at home and school, including waking up early, worshiping according to beliefs, regular exercise, consuming nutritious food, studying hard, social interaction, and sleeping early. This study used a descriptive qualitative approach, the research was conducted at SD Muhammadiyah 1 Banyuwangi with informants consisting of 5 teachers, 5 parents, and 15 students with various cognitive levels. Data were obtained through interviews, observation, and documentation, then analyzed using the Miles and Huberman model: data reduction, data presentation, and conclusion drawing. The results showed that the successful implementation of this habit depends on the synergy between teachers and parents. Teachers familiarize the values in the school culture and learning activities while parents reinforce them at home. The main challenges include limited parental involvement and uncontrolled use of gadgets affecting children's sleep patterns. The conclusion of the study confirms that strong collaboration between home and school can shape the character of children who are disciplined, responsible and emotionally stable. This study recommends further studies to develop a contextualized and sustainable implementation model.